Music production in Swedish higher education: history and future challenges - Gullö, Jan-Olof; Thyrén, David (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2020)
Although there is a growing interest for music production in Swedish higher education, where many students today study the subject, we argue that music production may in many ways still be noticed as a blind spot in research. This paper explores how research and education in music production has emerged, in Sweden but also internationally, against the background of the ongoing research project Searching for Sophia in music production. This project investigates how various aspects linked to music production and music education have contributed to the Swedish music industry’s international achievements. First, the development of music production courses and programmes in higher education is described, from the pioneering years in the 1980s until present. Next, we discuss key concepts in music production including the different phases of a music production and the role of the music producer. Thereafter we focus on four selected aspects of music production: creativity, innovation, motivation, and entrepreneurship. Further, future implications are discussed concerning the changes in how music is composed and produced, marketed, distributed, and how music is consumed today.